1991
DOI: 10.7326/0003-4819-114-2-1-107
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-Resistant Staphylococcal Colonization and Infection in a Long-Term Care Facility

Abstract: Colonization of the anterior nares by MRSA predicts the development of staphylococcal infection in long-term care patients; most infections arise from endogenously carried strains. Colonization by MRSA indicates a significantly greater risk for infection than does colonization by MSSA. The results offer a theoretic rationale for reduction in MRSA infections by interventions aimed at eliminating the carrier state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
150
3
10

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 364 publications
(171 citation statements)
references
References 29 publications
8
150
3
10
Order By: Relevance
“…Several studies have highlighted the relevance of this epidemiological aspect which might influence the infection control practices implemented by acutecare hospitals [18][19][20][21][22] but there are limited data on the relationship of MRSA colonization and the development of infection in residents of LTCFs [12,14]. This aspect has usually been assessed in settings where patients are at great risk of MRSA infection, such as intensive care units [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have highlighted the relevance of this epidemiological aspect which might influence the infection control practices implemented by acutecare hospitals [18][19][20][21][22] but there are limited data on the relationship of MRSA colonization and the development of infection in residents of LTCFs [12,14]. This aspect has usually been assessed in settings where patients are at great risk of MRSA infection, such as intensive care units [10].…”
Section: Discussionmentioning
confidence: 99%
“…5% [13] and a relative risk of 3 . 6 in MRSA carriers in LTCFs [12]. Persistent MRSA carriers are more often colonized at multiple sites, are more likely to transmit to others, and become infected than transient carriers [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the first follow-up year, we found that 56% of MRSA carriers, 32% of MSSA carriers, and 30% of non– S. aureus carriers developed skin infections. A similar study by Muder et al in a long-term care facility showed infection rates of 25%, 4%, and 4% for the same carriage groups, respectively, but patients were only followed while in the hospital and median duration of follow-up was <1 year for the carriage groups ( 24 ). Another prospective study of soldiers by Ellis et al found that 38% of MRSA carriers, 3% of MSSA carriers, and 2% of non– S. aureus carriers developed subsequent skin infections ( 18 ).…”
Section: Discussionmentioning
confidence: 81%
“…Risk factors found in these community settings are frequent skin-to-skin contact ( 11 , 12 , 14 , 15 ), sharing of personal items without frequent cleaning ( 11 14 ), and MRSA carriage ( 18 , 20 ). Nasal colonization is also a risk factor for infections in hospital settings ( 4 6 , 21 23 ) and long-term care facilities ( 24 , 25 ). However, all of these previous studies have used a case–control study design, making it impossible to determine if MRSA carriage preceded infection.…”
mentioning
confidence: 99%
“…Murder et al [24] evaluated the development of staphylococcal infection in methicillin-resistant (MRSA) and methicillin-susceptible (MSSA) S. aureus nasal carriers and found that 25% of patients who developed infection were MRSA carriers, whereas among MSSA carriers or non-carriers, as few as 4% and 4.5% respectively developed infections (73% of all MRSA infections occurred in nasal carriers of the microorganism). They also concluded that the management of carriers may be used as a control measure.…”
Section: Discussionmentioning
confidence: 99%